LOCAL WISDOM AND ENVIRONMENTAL CONSERVATION: English - Guci, Utari; Harahap, Rahimul (Trigin Institute, 2024)
The quality of nature affects the continuation of human life, after many disasters that befall human life. The more eager man wants to exploit nature and treat it for his own interests, the more destructive nature becomes. This research aims to obtain information from indigenous peoples about life that is one with nature, living together with nature, nature management and preservation can take place traditionally. Qualitative research using participant interviews and snow baal approach, data is reduced and analyzed from the beginning of the study. The results showed that traditional communities with simple patterns with a number of local wisdom have proven a harmonious relationship with nature. Without realizing it by indigenous peoples that the relationship of life between humans and nature is united in the form of environmentally ethical behavior; Appreciate and realize the unity of life between components that exist in nature, as well as the interdependence of life, between components in nature (ecosystems). Ecofeminism already exists in indigenous peoples, not only regulating relationships between humans, but also regulating relationships with the environment. Eco-friendly behavior is patterned into recommendations and prohibitions in dealing with nature.